Characteristics of the surface layer of selected glass-ionomer cements by inverse gas chromatography in increased humidity conditions - Batko, K.; Voelkel, A.; Andrzejewski, M.; Andrzejewska, E.; Limanowska-Shaw, H. (Polimery, 2022)
Theoretical fundamentals of inverse gas chromatography (IGC) method applied to evaluation of surface properties of various materials, especially glass-ionomer cements as the subjects of investigations, were presented. The values of dispersive component of surface free energy () of two such cements, used as the dental fillings, were determined by IGC (Table 1). The following parameters, except of the cement type, were investigated: relative humidity of carrier gas used in IGC method (RH = 60 or 80 %), type of medium for the sample storage before the measurements (water or artificial saliva) and storage time (up to 180 days). RH value appeared to be the most important parameter: at lower humidity of a carrier gas the surface activity of cements has usually been greater. Unambiguous determination of the effects of another parameters appeared to be impossible because of non-directed fluctuations of values. The results obtained suggest similar surface activity of both fillings.